Genome wide association analysis in a mouse advanced intercross line - Natalia M. Gonzales (Nature Portfolio, 2018)
Multigenerational outbred populations from an advanced intercross line (AIL) of mice represent useful resources for genome wide association analysis. Here, the authors analyze 1,063 LG x SM AIL mice to identify significant associations for 50 traits relevant to human health and disease.